How do skeletal morbidity rate and special toxicities affect 12-week versus 4-week schedule zoledronic acid efficacy? A systematic review and a meta-analysis of randomized trials. (October 2019) - Santini, Daniele; Galvano, Antonio; Pantano, Francesco; Incorvaia, Lorena; Rizzo, Sergio; Vincenzi, Bruno; Castellana, Luisa; Giuliana, Giovanna; Guadagni, Fiorella; Toia, Francesca; Tonini, Giuseppe; Russo, Antonio; et al.
Highlights: Zoledronic acid bisphosphonate has been demonstrated to provide benefits in bone metastases from solid tumors. Bone health parameters were skeletal morbidity rate (SMR), skeletal related events (SRE) and adverse events (AEs). Results support the 12-weeks zoledronic acid schedule as a valid options in breast and prostate cancer patients. Our meta-analysis supports the 12-weeks zoledronic acid schedule as a valid options in breast and prostate cancer patients. Abstract: Background: Zoledronic Acid is a bisphosphonate used in a 4-week schedule for the treatment of bone metastases. Some randomized trials supported its role also when administered every 12 weeks. Methods: we performed a systematic review and a meta-analysis in order to evaluate the two different schedules in terms of skeletal morbidity rate (SMR), skeletal related events (SRE) and adverse events (AEs). Results: our results showed a clinical difference favouring the 12-week schedule in terms of AEs (RR 1.17, 95% CI 1.06–1.29). No signifcant differences were found for SMR (RR 0.97, 95% CI 0.84–1.13) and SRE (RR 1.02, 95% CI 0.89–1.16). Conclusions: Our findings support in clinical practice the 12-week schedule an alternative to the standard 4-week schedule in advanced breast and prostate cancer, in particular when the clinical comorbidities of the patients suggest a higher risk of renal failure or hypocalcaemia.